STANDARD PIAWAIAN HALAL DI MALAYSIA MENURUT PERUNDANGAN, KELEBIHAN DAN KEKURANGAN(LEGISLATION, ADVANTAGES AND DISADVANTAGES OF HALAL STANDARDS MALAYSIA) (UMRAN - Journal of Islamic and Civilizational Studies, 2015)
Currently, halal products show tremendous growth internationally. The increased production of various products in the market led to the need of halal standard parallel. Therefore, this research is conducted to study the position of the Malaysian halal standard from legal perspective. The study also explores the advantages and disadvantages of the halal standard that is being implemented in Malaysia. The results of the analysis show that the Malaysian legislation pertaining to halal has been designated as early as the 70s. However, the legislation exists separately in different legal sections namely Food Act 1983, Trade Descriptions Act 1972 and the Consumer Protection Act. From the analysis of the advantages of the halal standard, it can be inferred that Malaysian guidelines for halal products is comprehensive notably with the aid of existing Islamic law that help authorities to monitor halal products in Malaysia as well as in export countries that recognize halal standard adopted by Malaysia. However, to date, there are still some drawbacks associated with the quality assurance that has been highlighted by the media and thus indirectly portray negative impact on Malaysia’s effort in developing the halal hub
Keywords: Halal Standards; Legislation; Advantages and Disadvantages